PENGEMBANGAN PARIWISATA MELALUI INTEGRASI PERENCANAAN SUMBER DAYA MANUSIA DENGAN PERENCANAAN STRATEGIS OBJEK WISATA TAMAN BUNGA MANOHARA - Hanung Eka Atmaja; Shinta Ratnawati (Jendela Inovasi Daerah, 2020)
Human resource planning determines in anticipating of future business, demand in the corporate environment, and discovers personal requests that arise from those needs. While human resource planning as a management process to determine how organization determines position. However, the link between human resource planning and strategic management is often overlooked. The research method uses an empirical qualitative design that is descriptive exploration to describe and explain the activities or objects under study relating to the study of phenomena in more detail or distinguish them from other phenomena. Through this process the company is expected to have Human Resources in the right amount, quality, place, time and produce long-term benefits for both individuals and organizations. The tourism sector is one of the sectors and the Indonesian government to generate foreign exchange, therefore the use, development, management and funding of tourism areas must receive serious attention from the government by involving the role of government agencies, stakeholders involved in participating share public relations. Human Resources planning must be integrated with the organization's short-term and long-term planning goals. The results of the evaluation of long-term HR planning are used as a basis for organizational succession planning. The planning process often does not run smoothly, because policy planning is not made in detail, resulting in a gap between company policy and personnel policy and its application in practice.